Effects of isometric exercises versus static stretching in warm-up regimens for running sport athletes: a systematic review - Ullman, Z. J.; Fernandez, M. B.; Klein, M. (International Journal of Exercise Science, 2021)
The objective of this review was to identify studies that report the pre-exercise effects of isometric exercise versus static stretching on performance and injury rates of running athletes in comparison to their outcomes. Seven electronic databases were searched: Cochrane, PEDro, CINAHL, PubMed, MEDLINE, SportDiscus, and GoogleScholar. Data was collected using an established PICO question, and assembled logic grid. The included articles were required to (1) assess running performance or injury prevention and (2) include isometric exercises/muscle activation and/or static stretching. Articles published prior to the year 2000, non-English, and non-human studies were excluded. Quality was assessed using the PEDro quality appraisal tool for RCTs, and NIH-NHLBI appraisal tool for others. The Cochrane collaboration tool for risk of bias as well as the PRISMA 2020 statement were also used in this review. In the nine articles appraised in the study, variables assessed included running economy, injury rate, soreness levels, sprint times, and countermovement and drop jump height. Static stretching demonstrated a significant negative effect on sprint performance and countermovement/drop jump height. It also demonstrated a decrease in variables associated with injury over extended periods and no impact on running economy. Isometric holds demonstrated no significant effect on sprint performance or countermovement/drop jump height. It also demonstrated decreases in soreness levels and no impact on running economy. Isometric holds have positive effects/fewer negative results on running athletes when compared to static stretching for pre-exercise performance. Research with decreased risk of bias is needed to determine maximal benefits from timing/dosage of isometric hold in warm-up.